Imponiendo derrotas a triunfos del pasado: corporizaciones de la memoria y el olvido en Los que van quedando en el camino de Guillermo Calderón 2010 - Hurtado, María de la Luz (Latin American Theatre Review, 2015)
Recent Chilean theatre, insisting on processing collective trauma, has developed procedures that bend canonic dramaturgies through staging in peculiar spaces and embodiments charged with symbolic weight, thus articulating the renewed critical horizon of post-dictatorship generations. This procedure is explored through the deconstruction of the theatrical, performative, and dramatic threads of Guillermo Calderón’s staging in 2010 of Aguirre’s text Los que van quedando en el camino. First staged in 1969 by DETUCH, the play was looked upon as the “right” performance, congruent with the utopic prerevolutionary times of its emergency. This study proposes that Calderón composes his production as an allegory of the personal/historical rub between the always declining and nonetheless persisting personal-historical urge towards memory, a process he claims is condemned to a catastrophic failure.